The efficacy and safety of combined GLP-1RA and basal insulin therapy among inadequately controlled T2D with premixed insulin therapy. Issue 10 (10th March 2023) - Liu, Jhih-Syuan; Su, Sheng-Chiang; Kuo, Feng-Chih; Li, Peng-Fei; Huang, Chia-Luen; Ho, Li-Ju; Chen, Kuan-Chan; Liu, Yi-Chen; Lin, Chih-Ping; Cheng, An-Che; Lee, Chien-Hsing; Lin, Fu-Huang; et al.
Abstract : This study investigated the effect of a combination of glucagon-like peptide-1 receptor agonist (GLP-1 RA) and basal insulin (BI) in poorly controlled type 2 diabetes mellitus previously treated with premixed insulin. The possible therapeutic benefit of the subject is mainly hoped to provide a direction for optimizing treatment options to reduce the risk of hypoglycemia and weight gain. A single-arm, open-label study was conducted. The antidiabetic regimen was switched to GLP-1 RA plus BI to replace previous treatment with premixed insulin in type 2 diabetes mellitus subjects. After 3 months of treatment modification, GLP-1 RA plus BI was compared for superior outcomes by continuous glucose monitoring system. There were 34 subjects at the beginning, 4 withdrew due to gastrointestinal discomfort, and finally 30 subjects completed the trial, of which 43% were male; the average age was 58 ± 9 years old, and the average duration of diabetes was 12 ± 6 years, the baseline glycated hemoglobin level was 8.6 ± 0.9 %. The initial insulin dose of premixed insulin was 61 ± 18 units, and the final insulin dose of GLP-1 RA + BI was 32 ± 12 units ( P < .001). Time out of range (from 59%–42%), time-in-range (from 39%–56%) as well as glucose variability index including standard deviation also improved, mean magnitude of glycemic excursions, mean daily difference and continuous population in continuous glucose monitoring system, continuous overall net glycemic action (CONGA). Also noted was a decrease in body weight (from 70.9 kg–68.6 kg) and body mass index (all P values < .05). It provided important information for physicians to decide to modify therapeutic strategy as individualized needs.